Cimarron [videorecording (DVD)] - Ruggles, Wesley, 1889-1972; Ruggles, Wesley, 1889-1972; Dix, Richard, 1893-1949; Dunne, Irene, 1898-1990; Taylor, Estelle, 1894-1958; O'Neil, Nance, 1874-1965; Collier, William, Jr; Ates, Roscoe, 1895-1962; Oliver, Edna May, 1883-1942; Ferber, Edna, 1887-1968 (Turner Entertainment Co. : Distributed by Warner Home Video, 2006)
"A nation rising to greatness through the work of men and women, new country opening, raw land blossoming, crude towns growing into cities, territories becoming rich states. In 1889, President Harrison opened the vast Indian Oklahoma lands for white settlement--2,000,000 acres free for the taking, poor and rich pouring in, swarming the border, waiting for the starting gun, at noon, April 22nd ..."--Prologue from title screens. Cimarron is a sprawling western saga, an earnest tale about empire building, and a film of its time, which viewers should keep in mind. It follows the adventures Yancey Cravat, a lawyer and newspaperman from Wichita, who joins the Oklahoma Territory land rush in 1889. Soon he and his family are citizens of Osage. Beset by wanderlust, Yancey joins the Cherokee Strip land rush in 1893, leaving wife Sabra behind to run the newspaper and raise their son, Cimarron. by 1907, Yancey is back at home as Oklahoma becomes a state. During the oil boom, he refuses to join a scheme to cheat the Indians out of their oil rich land, and then disappears again. In 1929, Sabra is elected Oklahoma's first Congresswoman, Cimarron is married to an Indian princess, and Yancey still hasn"t returned.